Alterations of perineuronal nets in the dorsolateral prefrontal cortex of neuropsychiatric patients - Julia Alcaide; Ramón Guirado; Carlos Crespo; José Miguel Blasco-Ibáñez; Emilio Varea; Julio Sanjuan; Juan Nacher (International Journal of Bipolar Disorders, 2019)
Abstract Background Alterations in the structure and physiology of interneurons in the prefrontal cortex (PFC) are important factors in the etiopathology of different psychiatric disorders. Among the interneuronal subpopulations, parvalbumin (PV) expressing cells appear to be specially affected. Interestingly, during development and adulthood the connectivity of these interneurons is regulated by the presence of perineuronal nets (PNNs), specialized regions of the extracellular matrix, which are frequently surrounding PV expressing neurons. Previous reports have found anomalies in the density of PNNs in the PFC of schizophrenic patients. However, although some studies have described alterations in PNNs in some extracortical regions of bipolar disorder patients, there are no studies focusing on the prefrontocortical PNNs of bipolar or major depression patients. For this reason, we have analyzed the density of PNNs in post-mortem sections of the dorsolateral PFC (DLPFC) from the Stanley Neuropathology Consortium, which includes controls, schizophrenia, bipolar and major depression patients. Results We have not observed differences in the distribution of PV+ cells or PNNs, or in the percentage of PV+ interneurons surrounded by PNNs. The density of PV+ interneurons was similar in all the experimental groups, but there was a significantly lower density of PNNs in the DLPFC of bipolar disorder patients and a tendency towards a decrease in schizophrenic patients. No differences were found when evaluating the density of PV+ cells surrounded by PNNs. Interestingly, when assessing the influence of demographic data, we found an inverse correlation between the density of PNNs and the presence of psychosis. Conclusions The present results point to prefrontocortical PNNs and their role in the regulation of neuronal plasticity as putative players in the etiopathology of bipolar disorder and schizophrenia. Our findings also suggest a link between these specialized regions of the extracellular matrix and the presence of psychosis.